Improving the Quality of Learning through Educational Supervision Projects and Tools - Cwisan Angeltri Zalukhu; Rahelia Simbolon; Theresia Revani Dianita Silaban (PT. Global Research Collaboration, 2025)
The quality of learning is a fundamental component in achieving educational goals. To enhance this quality, the implementation of project-based learning and the optimization of educational supervision tools emerge as complementary strategies. This article explores the integration between project-based learning, which fosters active student engagement, and structured supervision tools used by educators and school supervisors. The method employed in this study is a literature review and descriptive analysis of educational supervision practices and project-based instruction in schools. The findings indicate that the synergy between well-executed projects and effective supervision improves student motivation, creativity, and teacher professionalism. Therefore, improving learning quality can be holistically achieved through the integration of active learning strategies and continuous educational supervision.